Respuesta :
Basically all you’re doing is plugging in the inputs to the equations and see if they’re correct.
5(3)+4(-3)=3 this proves to be true
2(3)-5(-3)=21 not 19
5(3)+4(-3)=3 this proves to be true
2(3)-5(-3)=21 not 19
Answer:
(3,-3) is not a solution of the given system.
Solution:
The equations given in the problem are,
[tex]5x+4y=3[/tex] ----- (i)
[tex]2x-5y=19[/tex] ------------ (ii)
Now if (3,-3) is a solution of the system then both equation will satisfy by substituting the value of x as 3 and y as -3. If any of the equation does not satisfy with (3,-3) then this is not the solution i.e. the given value should satisfy both the equations to be a solution.
So, now substituting value of (x, y) as (3,-3) on equation (i) we get
[tex]5x+4y=3[/tex]
[tex]5 \times3 +4\times(-3) = 3[/tex]
[tex]15 -12 =3[/tex]
Here, [tex]3=3[/tex] --- (a) (satisfies the first equation)
Again substituting value of (x, y) as (3,-3) on equation (ii) we get
[tex]2x-5y=19[/tex]
[tex]2\times3-5\times(-3) = 19[/tex]
[tex]6+15 =19[/tex]
Here, [tex]21\neq 19[/tex] --- (b) (does not satisfy the second equation)
From (a) and (b) we can conclude that the value (3.-3) does not satisfy the second equation. So, this is not a solution of the system.